Increasing Dependency Ratios, Pensions, and Tax Smoothing - Tanzi, Vito.; Sadka, Efraim (Washington, D.C. : International Monetary Fund, 1998)
The implication of increasing dependency ratios for pay-as-you-go, defined-benefit pension programs are examined. Modifications aimed at smoothing contributions while maintaining benefits intact are analyzed for both open and closed economies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet